Factors Influencing Efficacy of Peripheral Corneal Relaxing Incisions during Cataract Surgery - Nino Hirnschall; Jörg Wiesinger; Petra Draschl; Oliver Findl (Journal of Ophthalmology)
Purpose. To evaluate influencing factors on the residual astigmatism after performing peripheral corneal relaxing incisions (PCRIs) during cataract surgery. Methods. This prospective study included patients who were scheduled for cataract surgery with PCRIs. Optical biometry (IOLMaster 500, Carl Zeiss Meditec AG, Germany) was taken preoperatively, 1 week, 4 months, and 1 year postoperatively. Additionally, corneal topography (Atlas model 9000, Carl Zeiss Meditec AG, Germany), ORA (Ocular Response Analyzer, Reichert Ophthalmic Instruments, USA), and autorefraction (Autorefractometer RM 8800 Topcon) were performed postoperatively. Results. Mean age of the study population n=74 was 73.5 years (±9.3; range: 53 to 90) and mean corneal astigmatism preoperatively was −1.82 D (±0.59; 1.00 to 4.50). Mean corneal astigmatism was reduced to 1.14 D (±0.67; 0.11 to 3.89) 4 months postoperatively. A partial least squares regression showed that a high eccentricity of the cornea, a large deviation between keratometry and topography, and a high preoperative astigmatism resulted in a larger postoperative error concerning astigmatism. Conclusions. PCRI causes a reduction of preoperative astigmatism, though the prediction is difficult but several factors were found to be a relevant source of error.